Upholding justice social, psychological and legal perspectives - Deb, Sibnath; Subhalakshmi, G.; Chakraborti, Kaustuv (Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2021)
This book critically examines the social, psychological and legal perspectives of justice. It brings together a wide range of contemporary and relevant issues relating to the gross violation of human rights and presents situation-based evidence from firsthand experiences of behavioral, social as well as legal professionals. It deals with themes such as civic and legal rights of children; dignity of the third gender in India; food justice in a welfare state; rights of disabled children; secret marriage of individuals with mental health challenges; and ethics and good governance. Topical and comprehensive, this book will be an excellent read for scholars and researchers of political studies, legal studies, human rights, psychology, behavioral studies, political sociology, sociology, development studies, governance and public policy, and South Asian studies. It will also interest policy makers, NGOs, activists and professionals in the field.
OCLC-licensed vendor bibliographic record.
Keywords: Human rights -- India; Social justice -- India; Children's rights -- India; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; POLITICAL SCIENCE / General; LAW / Constitutional